The Main Character's Jealousy as Seen in Gillian Flynn's Gone Girl: A Psychological Approach - Ganesh Yogi Prabowo; Astry Fajria (Universitas Ahmad Dahlan, 2021)
Jealousy is part of human's psychological condition. Similarly, Gillian Flynn employed the topic brilliantly in one of her works, Gone Girl. The present study entitled